From Anxiety To Emotional Stability: The Role of Emotional Maturity in Childbirth Anxiety - Wasis Purwo Wibowo; Yudho Bawono (Universitas Katolik Soegijapranata, 2026)
Pregnancy is often accompanied by anxiety, particularly as childbirth approaches, which may adversely affect the physical and psychological well-being of both the mother and the fetus. This study aimed to examine the role of emotional maturity in childbirth anxiety among pregnant women in Bangkalan Regency. It was hypothesized that emotional maturity significantly influences childbirth anxiety. This study used a quantitative approach using simple linear regression analysis. The participants comprised 100 pregnant women in Bangkalan Regency, aged 23–35 years, with a gestational age of more than 30 weeks. Participants were selected using purposive sampling. Data were collected using the Perinatal Anxiety Screening Scale (PASS) with 31 items and an Emotional Maturity Scale with 30 items. The results showed that emotional maturity had a significant effect on childbirth anxiety among pregnant women (F = 17.575, p 0.01; β = −0.402, t = −4.192, p 0.01). These findings indicate that emotional maturity plays a significant role in reducing childbirth-related anxiety among pregnant women in Bangkalan Regency. Specifically, pregnant women with higher levels of emotional maturity tend to experience lower levels of anxiety as they approach childbirth.